Implementation of Technometrics and AHP in Determining Indicators for Measuring The Technology Content of Halal Food MSMES in Tangerang Regency - Anni Rohimah; Rahmat Saputra; Eko Hadi Sucipto (Eduvest - Journal of Universal Studies, 2025)
The competitiveness of a nation no longer lies in the wealth of natural resources and labor, but rests on the ability to innovate and develop technology. One of the supporters of competitiveness is the existence of MSMEs. Currently, the government is implementing halal certification obligations for food MSMEs. To measure the content of technology in halal food MSMEs, measurements are needed using a questionnaire containing technology indicators. Technology is defined as physical things (Technoware), humans (Humanware), knowledge (Infoware), and social components (Orgware). This study uses technometric and AHP methods. The calculations showed that the indicators for Technoware are equipment maintenance, packaging equipment, equipment sophistication, and equipment that is easy to use. Indicators for humanware are experienced human resources, human resources with integrity, skilled human resources, never giving up human resources, and highly motivated human resources. Indicators for Inforware are Ease of Access to Info, Marketing Info, Licensing Info, and Cooperation Info. The indicators of the Orgaware Dimension are Leadership, Organizational Structure, MSME Community, and relationships.